Digital Marketing Training Towards Vocational Centers of Excellence: Pelatihan Digital Marketing Menuju SMK Pusat Keunggulan - Rika Septianingsih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
PK SMK is one of the government's programs to realize the ideal of educating the nationtion. SMK-PK has a program to develop certain skills and competencies so that the graduates produced are superior and absorbed by the industrial world. The University of Muhammadiyah Riau, as a companion higher education institution (PT), has a program that has been prepared based on the goals and objectives of SMK-PK. Digital marketing is one of eight (8) programs that will be fostered at SMKN-2 Tembilahan. SMKN 2 Tembilahan, one of the SMKs, headed for the Center of Excellence. Digital marketing is important for the business world. along with the development of the "4.0 revolution," where all lines of life are connected to technology. So with this training, it is hoped that teachers can improve their competence in the field of digital marketing. The participants in this training were teachers at SMKN-2 Tembilahan. Based on the evaluation obtained after this training, there was an increase in teachers' understanding of digital marketing. It is hoped that the competency of this training will continue to be upgraded so that the SMK Center of Excellence is realized.